Perceptions of Spruce Budworm Monitoring, Management, and Remote Sensing Technology in Maine’s Forest Sector - Foster, Allison; Rahimzadeh-Bajgiran, Parinaz; Weiskittel, Aaron; Daigneault, Adam (Maine Policy Review, 2024)
Eastern spruce budworm (Choristoneura fumiferana Clem; SBW) is a native forest pest that can severely damage spruce-fir forests in Maine. Monitoring SBW defoliation and populations is important to ensure forest managers make timely decisions regarding forest management. This research brief presents the results of a survey of Maine’s large forest owners and managers. Our findings indicate a need for clear policies and collaborations between forest organizations to prepare for a SBW outbreak. While many forest organizations use satellite imagery, personnel capacity and lack of knowledge are barriers to using remote sensing. We recommend strengthening forest health programs by hiring a remote sensing specialist and increasing knowledge and skills around remote sensing in Maine’s forest sector.